Getting to Know Indonesia Through Local Wisdom: Exploration of Indonesian Arts and Culture in the BIPA Program - Meilita Hardika; Octo Dendy Andriyanto (Universitas Muhammadiyah Malang, 2025)
The introduction of local wisdom is essential for enhancing foreign learners’ language skills and cultural awareness, as well as for helping them adapt and avoid culture shock during their stay in Indonesia. This study aims to explore Indonesian local wisdom through arts and culture in the teaching of Bahasa Indonesia for Foreign Speakers (BIPA) at Surabaya European School (SES). A qualitative method was employed with 17 intermediate-level BIPA students as participants. Data were collected through classroom observations, teacher interviews, and a literature review relevant to local wisdom, Indonesian arts and culture, and BIPA learning. The findings reveal that BIPA learning at SES takes place in an interactive and meaningful manner through the introduction of local wisdom and its values via music, visual arts, dance, traditional performances, “cultural corner” activities, and the introduction of Indonesian culinary culture. Cultural activities within BIPA learning provide learners with knowledge, skills, and an understanding of Indonesian local wisdom values. BIPA learning not only focuses on language but also offers learners an in-depth cultural experience. Local wisdom thus serves as a bridge for learners to understand both the language and culture of Indonesia.